ANALISA KELAYAKAN INVESTASI PENGGANTIAN MOTOR BOILER FEED PUMP (BFP) PLTU TANJUNG JATI B UNIT 1-2 MENGGUNAKAN METODE CAPITAL BUDGETING - purbowo, janu (Lembaga Pengembangan Kinerja Dosen, 2025)
PLTU Tanjung Jati B have capacity 2,640 MW Nett that provide around 11% of JAMALI electric load. PLTU Tanjung Jati B unit 1 – 4 use sub critical boiler to produce the superheated steam to rolling the steam turbine during Economic Continuous Rate (ECR) 100%. Based on rankine siklus, preliminary pressure is produced by Boiler Feed Pump (BFP) deliver the condensate water from Deaerator to Boiler Drum and increase the pressure from 8.33 bar to be 208.2 bar. Energy consumption of unit 1&2 is around 7.2 % equal to 732,583 mWh where the biggest consumption is to operate the BFP. Beside as the biggest consumer of energy, its history of the motors has been operated for 17 years, the motors during several times have get the trouble and affect to reliability and efficiency of the plant. The temperature of winding motor sometimes increased and reach more than 135 °C and cause the motor was trip. There are 5 alternatives be assessed and then be chosen the best alternative, the first assessment is by risk assessment, then capital budgeting and continue by sensitivity analysis. As Technical, alternative replace by new OEM motor and alternative rewinding the existing motor to OEM manufacture are feasible to be carried out, however based on capital budgeting, the replacing by new motor from OEM is the most feasible alternative with NPV 8.04 billion, PP 3.48 years and IRR 25.94%.